Paciente femenino de 3 años de edad diagnosticada con asma bronquial. - Carrillo Nájera, Angie Margarita (2021)
Asthma is a disease that affects the lungs. It is one of the most common long-term illnesses in children, although adults can also get it. The following is a case of a 3-year-old female patient, the same one who came to the office for an asthmatic attack, with the following symptoms, constant cough, shortness of breath, chest pain and decreased vesicular murmur. The methods that were applied for the management of the pathology were based on rescue therapy procedures with salbutamol in metered dose inhalers, 3 puffs every 20 minutes for two continuous hours, nebulizations with dexamethasone. Based on the treatments carried out, the patient had a very favorable evolution, a better countenance and immediate response could be observed since the procedures that were performed were of vital importance for her recovery, the patient was discharged so that she can continue with home treatment in the event of an asthma episode.